Combinatorial effects of geopropolis produced by Melipona fasciculata Smith with anticancer drugs against human laryngeal epidermoid carcinoma (HEp-2) cells - Bartolomeu, Ariane Rocha [UNESP]; Frión-Herrera, Yahima [UNESP]; Da Silva, Livia Matsumoto [UNESP]; Romagnoli, Graziela Gorete [UNESP]; De Oliveira, Deilson Elgui [UNESP]; Sforcin, José Maurício [UNESP] (Elsevier, 2016)
The identification of natural products exerting a combined effect with therapeutic agents could be an alternative for cancer treatment, reducing the concentration of the drugs and side effects. Geopropolis (Geo) is produced by some stingless bees from a mixture of vegetable resins, gland secretions of the bees and soil. It has been used popularly as an antiseptic agent and to treat respiratory diseases and dermatosis. To determine whether Geo enhances the anticancer effect of carboplatin, methotrexate and doxorubicin (DOX), human laryngeal epidermoid carcinoma (HEp-2) cells were treated with Geo alone or in combination with each drug. Cell growth, cytotoxicity and apoptosis were evaluated using 3-(4,5-dimethyl thiazol-2yl)-2,5-diphenyltetrazolium bromide (MTT) assay, lactate dehydrogenase (LDH) release, and flow cytometry. Scratch assay was used to analyze cell migration and transmission electron microscopy to observe morphologic alterations. The influence of Geo on drug resistance was also investigated assessing P-glycoprotein (P-gp) action. Geo inhibited cell proliferation and migration. The combination Geo + DOX led to the highest cytotoxic activity and induced apoptosis, leading to loss of membrane integrity. Geo had no effect on P-gp-mediated efflux of DOX. Data indicate that Geo combined with DOX could be a potential clinical chemotherapeutic approach for laryngeal cancer treatment.
Keywords: Apoptosis; Chemotherapeutic agents; Geopropolis; P-glycoprotein